Blended Learning in Post-Pandemic Era: from Students’ Perspective - Khasanah, Nurul; Rochmahwati, Pryla; Cabiles, Roldan C.; Amrizal, Amrizal (Educalingua Journal, 2023)
Coronavirus disease 2019 stroke the world at the end of 2019 and influenced greatly to all of the sectors. One of the sectors is education. Similarly, when the pandemic ended gradually in 2022, learning returned to normal but required gradual adjustments because both instructors and students had become proficient with online learning. Blended learning is a suitable teaching and learning strategy for the current environment. Blended learning is a combination of online and in-person instruction. Given the widespread use of blended learning today, the researcher intends to investigate students' attitudes toward blended learning in the post-pandemic period. This investigation included 29 students from the English Department at IAIN Ponerogo. The results indicated that the majority of students have a favorable view of blended learning. Two fair attitudes showed in student-student interaction and the contribution of blended learning toward the improvement of their skills.